2020
DOI: 10.1021/jacs.0c07531
|View full text |Cite|
|
Sign up to set email alerts
|

Reinforced Room-Temperature Spin Filtering in Chiral Paramagnetic Metallopeptides

Abstract: Chirality-induced spin selectivity (CISS), the effect of helical molecules acting as room temperature hard magnets that confer spin polarization to electrical current, is an intriguing effect with potential applications in nanospintronics. In this scenario, molecules that are paramagnetic as well as helical would introduce a new degree of freedom in the same nano-scale device that has not been explored so far. Here, in order to investigate this idea, we propose the preparation of self-assembled monolayers (SAM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 55 publications
6
69
0
Order By: Relevance
“…48 Following this idea, we recently showcased the combination of these features in the first report of spin filtering in a solid-state device based on a self-assembled monolayer prepared with Tb 3+ coordinated by an LBT peptide. 49 The active role of the paramagnetic ion was unambiguously confirmed by three independent experimental approaches: cyclic voltammetry (see Fig. 3, right), electrochemical impedance spectroscopy and local transport in solid state devices using liquid-metal drop contacts (see Fig.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…48 Following this idea, we recently showcased the combination of these features in the first report of spin filtering in a solid-state device based on a self-assembled monolayer prepared with Tb 3+ coordinated by an LBT peptide. 49 The active role of the paramagnetic ion was unambiguously confirmed by three independent experimental approaches: cyclic voltammetry (see Fig. 3, right), electrochemical impedance spectroscopy and local transport in solid state devices using liquid-metal drop contacts (see Fig.…”
mentioning
confidence: 81%
“…However, LBTs are more specific, moreover it is only in LBTs that a spintronic effect has been experimentally demonstrated due to the interaction between the current flowing through the chiral biomolecule and the paramagnetic lanthanide ion. 49 For the ordering of LBTs at least two other approaches are conceivable (for a more detailed discussion, see SI section S4):…”
Section: Further Approaches For the Biochemical Design Of Polynuclear Metallopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that the quantum yield of photoelectrons depended both on the relative polarization of the light, and the chirality of the molecules. They started the study of the main factors that influence the CISS effect using self-assembled monolayers (SAMs) of double-stranded (ds) DNA and oligopeptides, demonstrating that spin selectivity is correlated to the supramolecular organization of single molecules, and its magnitude increases with the length of the DNA strands or peptide sequence, respectively ( Carmeli et al, 2002 ; Ray et al, 2006 ; Göhler et al, 2011 ; Xie et al, 2011 ; Kettner et al, 2015 ; Aragonès et al, 2017 ; Kiran et al, 2017 ; Tassinari et al, 2018 ; Torres-Cavanillas et al, 2020 ). These studies pointed out the previously ignored role of the spin in electron-biomolecule interactions, as well as the potential of SAMs of chiral molecules that work as spin filters at room temperature ( Michaeli et al, 2016 ; Naaman et al, 2019 ).…”
Section: The Ciss Effectmentioning
confidence: 99%
“…This phenomenon is popularly known as the chirality-induced spin selectivity (CISS) effect. [137,[163][164][165][166] Mondal et al reported the formation of monolayer-scale chiral conducting polymer films using poly{[methyl N-(tert-butoxycarbonyl)-(S)-3-thienyl-L-cysteinate]-co-thiophene} (PCT-L), via electrochemical grafting on aNielectrode in the applied potential range of À0.1 to À0.8 Vvs. SCE (saturated calomel electrode) at 50 mV s À1 .…”
Section: Electrochemical Grafted Molecular Layers For Spintronic Studiesmentioning
confidence: 99%